The calculus tutoring book - Ash, Carol 1935- (IEEE Press, 1986)
"In this practical tutorial, a world-class expert shows you how to transform the promises of Telecommunications Management Network (TMN) into a reality. You will find a useful road map to the development of the standards underlying TMN and how to take the specifications of these standards and apply them to product development. Drawing from her professional experience as manager of a team implementing TMN standards, author Lakshmi G. Raman shows service providers what they can ask of their suppliers, helps developers grasp key insights into TMN specifications, and provides practicing telecommunications engineers with a clear guide on how TMN standards meet the overall goals of network management.